Whole-exome Sequencing and an iPSC-Derived Cardiomyocyte Model Provides a Powerful Platform for Gene Discovery in Left Ventricular Hypertrophy - Zhi, Degui; Irvin, Ryan; Gu, Charles; Stoddard, Alexander; Lorier, Rachel; Matter, Andrea; Rao, D C.; Srinivasasainagendra, Vinodh; Tiwari, Hemant K.; Turner, Amy; Broeckel, Ulrich; Arnett, Donna K. (Frontiers in Genetics, 2012)
Rationale: Left ventricular hypertrophy (LVH) is a heritable predictor of cardiovascular disease, particularly in blacks. Objective: Determine the feasibility of combining evidence from two distinct but complimentary experimental approaches to identify novel genetic predictors of increased LV mass . Methods: Whole exome sequencing (WES) was conducted in 7 African American sibling trios ascertained on high average familial LV mass indexed to height (LVMHT). WES identified 31,426 missense or nonsense mutations (MS/NS) which were examined for association with LVMHT using linear mixed models adjusted for age, sex, body weight, and family relationship. To functionally assess WES findings, human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CM) were stimulated to induce hypertrophy; mRNA sequencing was used to determine expression differences associated with hypertrophy onset. Results: After correction for multiple testing, 295 MS/NS variants in 265 genes were associated with LVMHT. We identified 44 of 265 WES genes differentially expressed (P<0.05) in hypertrophied cells. To further prioritize these 44 candidates, 7 supportive statistical and annotation-based criteria were used to evaluate the relevance of these genes. Five genes, HLA-B, HTT, MTSS1, SLC5A12, THBS1, were each supported by 3 criteria. THBS1 encodes an adhesive glycoprotein that promotes matrix preservation in pressure-overload LVH and harbors conserved and predicted damaging variants. Conclusions: Combining evidence from cutting-edge genetic and cellular experiments can enable identification of novel LVH risk loci.